Development and evaluation of a blocking ELISA for serological diagnosis of equine infectious anemia - Zhe, Hu (2023)
Equine infectious anemia (EIA) is an important viral disease characterized by persistent infection in equids worldwide. Most EIA cases are life-long virus carriers with low antibody reactions and without the appearance of clinical symptoms. A serological test with high sensitivity and specificity is required to detect inapparent infection. In this study, a B-cell common epitope-based blocking ELISA (bELISA) was developed using a monoclonal antibody together with the EIAV p26 protein labelled with HRP. The test has been evaluated against the standard and with field serum samples globally. This bELISA test can be completed within 75 min, and the sensitivity is higher than those of either the AGID or one commercial cELISA kit. This bELISA assay was 8–16 times more analytically sensitive than AGID, and 2 to 4 times more analytically sensitive than one cELISA kit by testing three sera from the USA, Argentina, and China, respectively. The 353 serum samples from Argentina were tested, in comparison with AGID, the diagnostic sensitivity and specificity of our bELISA assay were 100% (154/154) and 97.0% (193/199), respectively, and the accuracy of the bELISA test was 98.3%. The bELISA test developed in this study is a rapid, sensitive, specific method for the detection of EIAV infection, and could be a promising candidate for use in the monitoring of the EIA epidemic worldwide.